A New Murine Model of Chronic Kidney Disease-Mineral and Bone Disorder. (14th December 2017) - Frauscher, Bianca; Artinger, Katharina; Kirsch, Alexander H.; Aringer, Ida; Moschovaki-Filippidou, Foteini; Kétszeri, Máté; Schabhüttl, Corinna; Rainer, Peter P.; Schmidt, Albrecht; Stojakovic, Tatjana; Fahrleitner-Pammer, Astrid; Rosenkranz, Alexander R.; et al.
Abstract : Chronic kidney disease (CKD) is associated with mineral and bone disorder (MBD), which is the main cause of the extensively increased cardiovascular mortality in the CKD population. We now aimed to establish a new murine experimental CKD-MBD model. Dilute brown non-Agouti (DBA/2) mice were fed with high-phosphate diet for 4 (HPD4) or 7 (HPD7) days, then with standard chow diet (SCD) and subsequently followed until day 84. They were compared to DBA/2 mice maintained on SCD during the whole study period. Both 4 and 7 days HPD-fed mice developed phosphate nephropathy with tubular atrophy, interstitial fibrosis, decreased glomerular filtration rate, and increased serum urea levels. The abdominal aorta of HPD-treated mice showed signs of media calcification. Histomorphometric analysis of HPD-treated mice showed decreased bone volume/tissue volume, low mineral apposition rate, and low bone formation rate as compared to SCD-fed mice, despite increased parathyroid hormone levels. Overall, the observed phenotype was more pronounced in the HPD7 group. In summary, we established a new, noninvasive, and therefore easy to perform reproducible CKD-MBD model, which showed media calcification, secondary hyperparathyroidism, and low-turnover bone disease.